Análise da taxa de crescimento da arrecadação ICMS setorial do Estado do Ceará - Silva, José Carlos Barbosa da (2013)
The aim of this study is to analyze the behavior of the ICMS and its major components to ensure a proper diagnosis about these series for public policy formulation. The methodology used is based on Perron and Yabu (2009a, 2009b), which proposes a trend model based in technique of Nearly Feasible Generalized Least Squares. The data used refer to the ICMS collection, in addition to its main macrosegments, namely Eletric Power, Communication & Fuels, and were collected from SEFAZ-CE. Furthermore, the information are monthly and cover the period from January 1990 to August 2012. The results high light that only ICMS collection presented a trajectory with a growth rate significantly, while the collection of macrossegment of Eletric Power grew at a steady rate, while the fuel sector showed a positive growth rate. In the Communication segment revenues grew at a decreasing rate.